Embodiment of War in Contemporary Graphic Printing in the Kurdistan Region / Iraq - Hemn Yahya Mohammed Noori; Rebwar Said Rashid (QALAAI ZANIST JOURNAL, 2024)
This paper is dedicated to the study of (Embodiment of War in Contemporary Graphic Printing in the Kurdistan Region / Iraq), which consists of four parts. The first part is devoted to presenting the research problem, importance, objectives and limitations of the research, which is limited to revealing the characteristics of contemporary graphic works by Kurdish artists in Kurdistan Regional Government cities, during the period 2016-2022 In terms of language, terminology and procedural definitions. The second part is prepared as a theoretical framework, which includes three sections. Section 1: A brief overview of the concept and history of war in the world through some different printing methods used. The third section is related to the history of contemporary graphic art in Kurdistan. The third part presents the methods and procedures of analysis. The descriptive method of analysis begins with the collection of works of art and ends with the examples of the graphical and technical characteristics of each of the examples, Chapter Four consists of the conclusions and results of each chapter from the examples and the graphic and technical characteristics of each of the examples.